US in NL : Amerikaanse Kunst in Nederlandse Musea 1945-2002 - Schenk, Ruud; Sobel, Clifford M. (Utrecht : Centraal Museum Utrecht, 2004)
Andre, Carl ; Arneson, Robert ; Barney, Matthew ; Calder, Alexander ; Riverhead (New York) ; Gober, Robert ; Guston, Philip ; Hanson, Duane ; Haring, Keith ; Hesse, Eva ; Johns, Jasper ; Judd, Donald ; Kelley, Mike ; Kelly, Ellsworth ; Kienholz, Edward ; de Kooning, Willem ; Koons, Jeff ; LeWitt, Sol ; Lichtenstein, Roy ; Louis, Morris ; Mangold, Robert ; Marden, Brice ; de Maria, Walter ; Martin, Agnes ; McLean, Richard ; Morley, Malcolm ; Morris, Robert ; Nauman, Bruce ; Newman, Barnett ; Noguchi, Isamu ; Oldenburg, Claes ; Paschke, Ed ; Pollock, Jackson ; Rauschenberg, Robert ; Rhoades, Jason ; Rothko, Mark ; Ryman, Robert ; Salle, David ; Schnabel, Julian ; Segal, George ; Serra, Richard ; Serrano, Andres ; Sherman, Cindy ; Smith, David ; Stella, Frank ; Turrell, James ; Viola, Bill ; Voulkos, Peter ; Warhol, Andy ; Weiner, Lawrence ; Zwillinger, Rhonda
Bibliog., tent. p. 232-235
Engels
Nederlands
boek
Keywords: Nederland; U.S.A.; Verenigde Staten van Amerika